UNDERSTANDING THE E-PURCHASING IN FIRST CITY PROVIDENTIAL COLLEGE CAFETERIA - Abaigar, Raisa Joan; Naig , Anne Michelle; Bisquera , Carlo; Baldonado , Daniella; Comprado, Kimberly (International Journal of Psychosocial Rehabilitation, 2020)
ABSTRACT:Purchasing is the activity of acquiring goods or services to accomplish the goals of an organization. These are to maintain the quality and value of the product to minimize cash tied up in inventory and maintain the flow of input and output procedure. In our generation most of the young people are usually taking advantage of technology such as entertainment, saving time, creating new things and its convenience.